Kecemasan Atlet Panjat Dinding Sebelum Pertandingan Pada Event Green Campus Wall Climbing Competion Tahun 2023 - Al Farid, Khabib; Kurniawan, Wing Prasetya; Himawanto, Wasis (Journal of Physical Activity and Sports (JPAS), 2024)
The purpose of preparing this research is to find out whether there is a feeling of anxiety experienced by a wall climbing athlete before a competition, with the method used, namely a survey, including quantitative descriptive research. The respondent in this study was a student or high school level athlete whose age range was around 16 to 18 years with a total of 53 respondents. Because the sample in this study had a population of 53 people, less than 100 people, the number of samples was taken as a whole or census technique. Researchers, to collect data, researchers distributed questionnaires that had previously been validated and afterwards analyzed using simple linear analysis in the SPSS 16 application. Based on After collecting and processing the data, the researcher got the results, namely that before the match (Y), the significant value was 0.000, because the probability of 0.000 < 0.05, H? was rejected and H? was accepted. It can be concluded that there is anxiety felt by wall climbing athletes before the competition at the 2023 Green Campus Wall Climbing Competition Event.